Respuesta :

yoco63
f(x) = 7/x
g(x)=x²+10

Then f(g(x))= 7/(x²+10)

By the way    g(f(x))=(7/x)² + 10
 

Answer:

  • f(x) = [tex]\frac{7}{x^{2} }[/tex] + 10
  • g(x) =  [tex]\frac{7}{x^{2} }[/tex]

Step-by-step explanation:

Given that:

y = f(g(x)) = [tex]\frac{7}{x^{2} }[/tex] + 10

It is obviously that g(x) is put as an independent variable of f(x) to have the equation of y written above.

So

  • f(x) = [tex]\frac{7}{x^{2} }[/tex] + 10
  • g(x) =  [tex]\frac{7}{x^{2} }[/tex]

Hope it will find you well.